The answer can be in the form of two defined constants: $$A = \frac{1}{1^1}+\frac{1}{2^2} + \frac{1}{3^3} + \cdots$$ $$B = \frac{1}{2^2} + \frac{1}{4^4} + \frac{1}{6^6} + \cdots $$

I would highly appreciate it if you included your thought process in the answer itself.

As pointed out by zz20s , the answer to this integral can be seen on the wikipedia page: Sophomore's dream and the page accompanies a proof too

  • 2
    $\begingroup$ Sophomore's dream $\endgroup$ – zz20s Jan 9 '18 at 14:47
  • $\begingroup$ $$e^{x\log x}=\sum_{n\geq 0}\frac{(x\log x)^n}{n!}$$ and $$\int_{0}^{1}(x\log x)^n\,dx = \frac{(-1)^n n!}{(n+1)^{n+1}}$$ so the answer is $A-B$. $\endgroup$ – Jack D'Aurizio Jan 9 '18 at 14:58
  • $\begingroup$ It should be $A - 2B$, shouldn't it? $\endgroup$ – Arpit Saxena Jan 9 '18 at 15:06
  • $\begingroup$ Your question is a part of: math.stackexchange.com/questions/2019859/… $\endgroup$ – user90369 Jan 9 '18 at 15:50

Note: there is no known closed form for $\int x^x \, \mathrm dx$.

But since we have bounds, we can use froggie's approach in this answer.

Recall that: $$\int_0^1 x^x\, \mathrm dx = \sum_{k=0}^\infty \frac{1}{k!}\int_0^1x^k(\log x)^k\, \mathrm dx$$

Make the substitution $u = -\log x$

$$\int_0^1 x^x\, \mathrm dx = \sum_{k=0}^\infty \frac{1}{k!}\int_0^1x^k(\log x)^k\, \mathrm dx = \sum_{k=0}^\infty \frac{(-1)^k}{k!}\int_0^\infty e^{u(k+1)}u^k\, \mathrm du$$$$ = \sum_{k=0}^\infty \frac{(-1)^k}{k!}\frac{1}{(k+1)^k}\int_0^\infty e^{u(k+1)}((k+1)u)^k\, \mathrm du$$

Make the substitution $t = (k+1)u$

$$\sum_{k=0}^\infty \frac{(-1)^k}{k!}\frac{1}{(k+1)^k}\int_0^\infty e^tt^k\, \mathrm dt = \sum_{k=0}^\infty \frac{(-1)^k}{(k+1)!}\frac{1}{(k+1)^k}\Gamma(k+1),$$ where $\Gamma$ is the usual Gamma function. Since $\Gamma(k+1) = k!$, the final expression is $$ \sum_{k=0}^\infty \frac{(-1)^k}{(k+1)^{k+1}} = \sum_{n=1}^\infty \frac{(-1)^{n-1}}{n^n}$$


I have written a detailed explanation to find the integral of a general expression of the form $f(x) =x^{cx^a} $ from $0$ to $1$ here.

$$\int_{0}^{1} x^{cx^a}\, dx = 1- \frac{c}{(a+1)^2} + \frac{c^2}{(2a+1)^3} - \frac{c}{(3a+1)^4}+\ldots$$

On substituting $c =1$ and $a=1$, we get the desired result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.